Comparative Analysis of the Preschool Education System in Developed Countries - Shakhnoza Khojimirzayeva (Indonesian Journal Publisher, 2026)
Preschool education plays a critical role in shaping a child’s future. It is during these early years that children begin to develop key cognitive, emotional, and social skills that lay the foundation for lifelong learning. As the global focus on early childhood education grows, parents and educators alike are looking at which countries provide the best preschool education. This article delves into the strengths and weaknesses of preschool systems around the world, examining what makes them successful and which countries stand out for their excellence in early education. The results showed that an effective preschool education model is characterized by child-centered pedagogy, play-based methodology, high professional training of teachers, and quality monitoring. Adapting international experience to the national system is an important scientific and practical resource.